Basics of game design - Moore, Michael E. (A K Peters/CRC Press, 2016)
This book is for anyone wanting to become a professional game designer. Focusing on creating the game mechanics for data-driven games, it covers role-playing, real-time strategy, first-person shooter, simulation, and other games. Written by a 25-year veteran of the game industry, the guide offers detailed explanations of how to design the data sets used to resolve game play for moving, combat, solving puzzles, interacting with NPCs, managing inventory, and much more. Advice on developing stories for games, building maps and levels, and designing the graphical user interface is also included. Features include: Covers the mechanics behind creating data-driven games, including role-playing and real-time strategy games; Explains how to design the data sets used to resolve game play; Offers recommendations on developing stories, building maps and levels, and designing the GUI; Provides many real examples and practical details, including screenshots of games.